IOT integration of a mobile application with a controller-based system: A - Pang, Bryan Seng Keong (Nanyang Technological University, 2023)
Students enrolled in Nanyang technological University (NTU) often opt to choose on-campus accommodations owing to the remote and slight inaccessibility of the NTU campus. The current standing of 14,000 students living on campus constitutes 44% of the entire student population: almost 1 in every 2 NTU students [1].These on campus accommodations are known as halls and they provide students with some amenities such as dining options as well as shower and laundry facilities. However, due to limited space, most halls have limited laundry facilities which serve the student population at a ratio of approximately 1:70 [1]. This scarcity creates a negative laundry experience for students as they will need to spend their time to queue and compete for the limited facilities. This problem becomes further exacerbated during peak usage periods when even more students queue and compete for the same facilities. Students also tend to forget some of their laundry items which are often lost along the way, with little hope of the owner reclaiming them. Furthermore, the laundry facilities also require new $1 coins for operation which are scarce amid NTU’s drive towards a cashless campus environment [2].All the hassle and inconvenience created by this scarcity could be avoided and the time could be directed to more productive tasks. A survey was carried out to better understand the current sentiments on campus accommodations for the current hall laundry facilities due to the lack of existing data. When asked about the satisfaction of laundry facilities in hall, 70% of residents stated that they were dissatisfied with the current facilities [3]. However, many still choose to use these facilities as they cited reasons such as costs and lack of alternative options. When asked if they would like new features such as cashless payments and booking systems, to improve the availability and convenience of laundry facilities, a resounding 100% of the residents responded with “strongly agree” [3]. This shows that huge areas of improvements for the current laundry systems exist, and this project can help to fill in these gaps. This project aimed to create and design a mobile application for users to book and pay for their laundry runs. The app was designed to display booking timeslots for users to better plan and manage their time. An integrated e-wallet allows students to seamlessly pay for their laundry thus eliminating the need for new $1 coins. An integrated lost and found feature allowed users to report and find their lost items thus giving users a better chance at recovering their items.